2020
DOI: 10.1212/nxi.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

MS optic neuritis-induced long-term structural changes within the visual pathway

Abstract: BackgroundThe visual pathway is commonly involved in multiple sclerosis (MS), even in its early stages, including clinical episodes of optic neuritis (ON). The long-term structural damage within the visual compartment in patients with ON, however, is yet to be elucidated.ObjectiveOur aim was to characterize visual system structure abnormalities using MRI along with optical coherence tomography (OCT) and pattern-reversal visual evoked potentials (VEPs) depending on a single history of ON.MethodsTwenty-eight pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…The changes in HON reported in the present and in previous studies might be related to retrograde degeneration of optic nerve axons and RGC bodies following a demyelinating event at the level of the optic nerve or even posterior to it [ 14 ]. In accordance, previous combined diffusion magnetic resonance imaging (MRI) and OCT studies reported retrograde, i.e., GCIPL/pRNFL, as well as anterograde, i.e., optic radiation, transsynaptic degeneration [ 23 ] and associated brain volume reduction [ 24 ].…”
Section: Discussionsupporting
confidence: 82%
“…The changes in HON reported in the present and in previous studies might be related to retrograde degeneration of optic nerve axons and RGC bodies following a demyelinating event at the level of the optic nerve or even posterior to it [ 14 ]. In accordance, previous combined diffusion magnetic resonance imaging (MRI) and OCT studies reported retrograde, i.e., GCIPL/pRNFL, as well as anterograde, i.e., optic radiation, transsynaptic degeneration [ 23 ] and associated brain volume reduction [ 24 ].…”
Section: Discussionsupporting
confidence: 82%
“…Optical coherence tomography can qualitatively and quantitatively measure changes of ganglion cell‐inner plexiform layer (GCIPL) around fovea and of unmyelinated optic nerve fiber layer (RNFL) in the papilla 5,6 . Optical coherence tomography has been validated as a sensitive and reliable tool to quantify inflammation, axonal loss and neurodegeneration in MS 7,8 and is increasingly used to monitor first‐order neurons of the afferent visual pathway in the retina 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…2 So far, researchers have not succeeded in untangling these effects. In addition, the study of Pawlitzki et al 4 does not shed light on this enigma: the frequency of lesions in the optic radiation is lower in the non-ON group, and the extent of ON-independent visual pathway damage in this cohort could not be evaluated because the study did not include healthy controls.…”
Section: Describementioning
confidence: 94%
“…Interestingly, the thickness of the primary visual cortex was neither associated with optic radiation DTI parameters nor with RNFL and GCIPL thinning. 4 DTI and retinal atrophy have emerged as important outcome measures in clinical MS research. 1 However, to widely implement OCT and DTI for the individual monitoring of disease progression and treatment response, we still lack important pathologic and technical considerations.…”
Section: Describementioning
confidence: 99%
See 1 more Smart Citation